Comparison of wireless and wired alarm devices for nocturnal enuresis treatment. Issue 1 (4th November 2022) - Watanabe, Tsuneki; Ikeda, Hirokazu; Ono, Takahiro; Oyake, Chisato; Watanabe, Yoshitaka; Fuyama, Masaki
Abstract: Background: In monosymptomatic nocturnal enuresis (MNE) treatment, enuretic alarm devices are the first recommended treatment option. This study aimed to compare retrospectively the effectiveness of wearable wireless and wired alarm devices for MNE treatment in children aged 6–14 years. Methods: All children aged 6–16 with MNE who underwent alarm therapy as outpatients were included. A wired alarm device was used from 2012 to 2015, and a wireless alarm device was used from 2016 to 2019. The primary outcomes were the dropout rates during therapy and at last follow up. The full response(14 consecutive dry nights) and the partial response rate during therapy were also assessed. Results: Of the 173 patients enrolled, 75 and 98 used a wired and a wireless alarm device, respectively. The dropout rate at the last visit was significantly lower in the wireless alarm group than that in the wired alarm group (6.1% vs. 20.0%; P = 0.006). The full response(FR) rate was significantly higher in the wireless alarm group than these in the wired alarm group at 4, 12, 24 weeks (4 weeks: 11.2% vs. 1.3%, P = 0.011; 12 weeks: 31.9% vs. 13.5%, P = 0.005; 24 weeks: 72.9% vs. 39.7%, P < 0.0001). Conclusions: Wireless alarm therapy for MNE had lower attrition rates and a higher rate of FR than wired alarm therapy.